How do health practitioners in a large Australian public hospital identify and respond to reproductive abuse? A qualitative study - Laura Tarzia; Molly Wellington; Jennifer Marino; Kelsey Hegarty (Elsevier, 2019)
Abstract Objective: Reproductive abuse is defined as a deliberate attempt to control or interfere with a woman's reproductive choices. It is associated with a range of negative health outcomes and presents a hidden challenge for health practitioners. There is a dearth of research on reproductive abuse, particularly qualitative research. This study aims to address this gap by exploring how health practitioners in a large Australian public hospital identify and respond to reproductive abuse. Methods: We conducted semi‐structured interviews with n=17 health practitioners working across multiple disciplines within a large metropolitan public hospital in Victoria. Data were analysed thematically. Results: Three themes were developed: Figuring out that something is wrong; Creating a safe space to work out what she wants; and Everyone needs to do their part. Conclusions: Practitioners relied on intuition developed through experience to identify reproductive abuse. Once identified, most practitioners described a woman‐led response promoting safety; however, there were inconsistencies in how this was enacted across different professions. Lack of clarity around the level of response required was also a barrier. Implications for public health: Our findings highlight the pressing need for evidence‐based guidelines for health practitioners and a 'best practice' model specific to reproductive abuse.